A study on illegal occupation and operation of landuse categories in Perak: a case of state land - Mohamed Osman, Mariana; Shuid, Syafiee; Bachok, Syahriah; Abdullah, Muhammad Faris; Ibrahim, Mansor; Hj. Mohd. Noor, Norzailawati (2016)
This study concerns on illegal occupation and operation of state land in Perak. In 2014, more than 17,000 hectares of land in Perak have been illegally cleared, resulting in the state government losing hundreds of millions of ringgit in revenue. The state government of Perak has introduced Rehabilitation program in 2011 under the scheme of ‘Pelan Tindakan Anti Usaha Haram (PETAH). However the program is still being continue till 2016 and have not able to address the problem totally. Therefore, this study is undertaken to identify the issues related to the illegal land occupation and operation on Perak state land and the potential income to the state, as well as to provide strategies and solutions to overcome the issues. Inventory survey is proposed to assess the physical condition of the selected case study area. Secondary data and interview analysis will highlight issues regarding to land issues, state revenue matters and environmental pollutions. Under the PETAH scheme most of the identified land has been alienated to the State Agencies such as PKNP, MB Inc etc with minimal charges. The outcome for this study will help to identify the current issues and problems regarding illegal occupation of state land and the potential revenue the Perak state would be able to collect if the disposal of the land through land alienation.